2013
DOI: 10.1111/joa.12041
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental ratios and logarithmic periodicity in human limb bones

Abstract: Fundamental mathematical relationships are widespread in biology yet there is little information on this topic with regard to human limb bone lengths and none related to human limb bone volumes. Forty-six sets of ipsilateral upper and lower limb long bones and third digit short bones were imaged by computed tomography. Maximum bone lengths were measured manually and individual bone volumes calculated from computed tomography images using a stereologic method. Length ratios of femur : tibia and humerus : ulna w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
(44 reference statements)
1
24
0
1
Order By: Relevance
“…In our view, our results suggest that long bone length, particularly the differential growth effect reflected in UFR, is a potential marker of pubertal organizing hormone effects. Research pertaining to forming limb ratios is rare, which is surprising given the very conserved mathematical relationships they yield (Pietak et al 2013). And if such ratios are calculated, researchers often seem to focus on within-extremity ratios like between ulna and radius (or humerus) or between tibia and fibula (Brons et al 1990;Pietak et al 2013).…”
Section: Long Bone Length As a Marker Of Pubertal Organizing Hormone mentioning
confidence: 99%
“…In our view, our results suggest that long bone length, particularly the differential growth effect reflected in UFR, is a potential marker of pubertal organizing hormone effects. Research pertaining to forming limb ratios is rare, which is surprising given the very conserved mathematical relationships they yield (Pietak et al 2013). And if such ratios are calculated, researchers often seem to focus on within-extremity ratios like between ulna and radius (or humerus) or between tibia and fibula (Brons et al 1990;Pietak et al 2013).…”
Section: Long Bone Length As a Marker Of Pubertal Organizing Hormone mentioning
confidence: 99%
“…The anthropometric relations between the clavicle and the ulna is an unknown issue and there are very limited studies focusing on this issue [1,2,5]. Our study revealed that there are fixed proportions between ulna and the clavicle lengths.…”
Section: Discussionmentioning
confidence: 50%
“…Mathematical relationships between bones lengths and volumes have been evaluated to improve our understanding of normal and disordered growth, stature estimation, and biomechanics [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But fascination with the GR is not confined to mathematicians. Biologists, artists, musicians, architects, psychologists, historians, and even mystics have pondered and debated the basis of its ubiquity and appeal (Livio, 2002;Lu and Steinhardt, 2007;Newell et al, 2008;Pietak et al, 2013;De Campos, 2014).…”
Section: Introductionmentioning
confidence: 99%